Designing an Emotion-Based Online System for English Language Teaching - İbrahim Enes Öner; Hasan Karal (Uluslararası Türk Eğitim Bilimleri Dergisi)
The aim of this study is to design an emotion-based system for the basic skills of the fifth-grade English course in online learning environments. The Design-Based Research (DBR) method was employed for designing this environment. Literature review, observation form, rubric, and semi-structured interview form were used as data collection tools in the DBR process. As a result of the research, an environment design framework was proposed that includes solutions to the problems, cognitive deficiencies, emotion analysis, and affective problems encountered by fifth-grade middle school students in developing basic skills in foreign language learning. In this design, emotion analysis, which is one of the sub-units of artificial intelligence, was integrated into the content presented to the students and the activities for basic skills. Within the scope of the research, activities targeting four fundamental skills for language learning were presented. Consequently, an emotion-based environment was created in which fifth-grade students can develop these basic language skills, reading, writing, speaking, and listening.